A new species of Cyclogomphus Selys, 1854 (Insecta: Odonata: Gomphidae) from the Western Ghats, India with comments on the status of Cyclogomphus vesiculosus Selys, 1873 - Rangnekar, Parag; Dharwadkar, Omkar; Sadasivan, Kalesh; Subramanian, K.a. (Zootaxa, 2019)
A new species of Cyclogomphus Selys, 1854 is described from the Western Ghats of India based on male and female specimens collected from Goa and Kerala states. The new species differs from all the known species of Cyclogomphus in the shape of the anal appendages as well as the thoracic and abdominal markings. We also provide here an updated key to the Cyclogomphus species and comment on the status of Cyclogomphus vesiculosus Selys, 1873.